Persistent organic pollutants (POPs) in fish (Somniosus microcephalus, Gadus morhua, Gadus ogac, Reinhardtius hippoglossoides) from Greenland seawaters - Salvatore Cotronei (Università degli Studi di Siena, 2018)
Persistent organic pollutants (POPs) include several groups of industrial chemicals, pesticides or technical by-products with similar structures and chemical-physical properties. Their occurrence in Arctic wildlife has been documented since the beginning of the 1970s. The Arctic region is reported to be a “cold trap” for these chemicals that have been transported over long distances. In addition, due to the low temperature, limited biological activity and minimal incidence of sunlight, POP degradation is very slow in this remote area. The Greenland Shark Somniosus microcephalus is a top predator of cold seawaters that may reach a total length of up to six metres. For this reason, it is one of largest shark species in the world and presumably the largest fish in the Arctic. Very little is known about its biology including migrations or habitat preferences; however, a number of studies demonstrate that S. microcephalus may extend from the temperate North Atlantic Ocean to the Arctic Ocean, hunting actively throughout the water column in the Arctic Sea. Considering that the S. microcephalus is an opportunistic top predator, extremely long-lived with slow growth, the bioaccumulation process of pollutants generated by human activities might be enhanced. The aims of this thesis were firstly to assess the concentrations of organochlorine pesticides (OCPs), polychlorobiphenyls (PCBs), brominated flame retardants (BFRs), polychlorinated dibenzo-p-dioxins (PCDDs) and polychlorinated dibenzofurans (PCDFs) in the liver and muscle samples of S. microcephalus from Greenland seawaters and, secondly, to investigate whether POPs concentration is correlated to lipid content, gender and age. In addition, concentrations of DDT, PCB, polybrominated diphenyl ethers (PBDEs), hexabromocyclododecane (HBCD) in the stomach contents of the Greenland shark and in the muscle of its prey (codfish and Greenland halibut) were measured to evaluate if biomagnification processes may occur. In the Greenland shark, the lipid content was 48 ± 10% in ...